Top management turnover: the role of governing board structures - Rutherford, Amanda; Lozano, Jon (2018)
The convergence of performance accountability policies, a graying bureaucracy, and shorter executive tenures highlights the timeliness of investigating executive turnover. Prior public administration research has examined pull and push factors linked to these departures, but it has yet to fully explore the influence of governing board structures and political pressures that stem from such structures. Using data on 123 public four?year research universities in the United States from 1993 to 2012, this article finds that governing board structures play a pivotal role in predicting the departure decisions of university presidents. While the size of the board increases the risk of departure, boards overseeing multiple institutions and boards with a faculty or student representative lower the risk of departure. Additional evidence suggests that both the share of gubernatorial and legislative appointees on the board and the party division of the legislature have a direct influence on departure. - Reproduced.
Keywords: Higher education - U.S.A.; Public administration